Total quality management (TQM) implementation among ISO 9001 registered construction companies in South Africa - Morumudi, Mokopi Petrus (My University, 2017)
Purpose: There has been much assertion about how ISO 9001 facilitates TQM implementation among ISO 9001 registered construction companies. However, the success rate of TQM implementation among ISO 9001 registered companies varies. The aim of this study was to investigate TQM implementation among ISO 9001 registered construction companies in South Africa. Three objectives were also established to aid in achieving the aim. Methodology: A cross-sectional survey design using structured questionnaire to collect quantitative and qualitative data was adopted. Respondents were purposively sampled among ISO 9001 registered construction companies in South Africa. 70 completed questionnaires were obtained from the target of 100. Text-based (i.e., qualitative) data were analysed using qualitative content analysis while quantitative data were analysed descriptively. Findings: The main three findings include: (1) the prevalence of defining quality as meeting clients’ expectations and assessing quality through internal inspection; (2) highest level of agreement on TQM being implemented through checking design conformance to standards and lowest level of agreement on formal training on TQM; and (3) customer feedback exercises and supplier relationship were indicated as being the least implemented ISO 9001 principles. Implications: The main practical implication of this study is identifying how TQM is being implemented among ISO 9001 registered construction companies in South Africa and the challenges they face. The main theoretical implication is being able to add to the existing studies validating ISO 9001 registered construction companies can and should implement TQM across their processes. Limitations: The main limitation has been restricted to not collecting data on the professional backgrounds and years of experience of the study participants. A finding during the pilot testing necessitated the preference to indicate job roles as against professional backgrounds.
Thesis is submitted in partial fulfilment for the degree of Masters of Science in Building (Project Management in Construction) to the Faculty of Engineering and the Built Environment, School of Construction Economics and Management at the University of the Witwatersrand, Johannesburg, 2017
Keywords: Total quality management--South Africa; Construction industry--South Africa--Management